2007
DOI: 10.1111/j.1365-246x.2007.03356.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the basin and fault geometry from the multichannel seismic reflection data in the Tekirdağ Basin, Marmara Sea, Turkey

Abstract: S U M M A R YDetermination of the fault geometry in the Marmara Sea has been a major problem for the researchers after the occurrence of the 1999 August 17 Golcuk (M = 7.4) earthquake. To shed a light to the problem we applied the pre-stack Kirchhoff depth migration technique to the multichannel seismic reflection data of three profiles to investigate the basin and fault geometry in the Tekirdag Basin in the western Marmara Sea. The boundary of the basin and its sediments were revealed in N-S and NE-SW directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Later, studies (Okay et al, 2004;Seeber et al, 2004;Kanbur et al, 2007) have shown that this interpretation is inconsistent with the land data requiring north-dipping reverse fault, indicating an obvious misinterpretation of the seismic profile by Okay et al (1999). At that point, the main question is why and how this misinterpretation is possible.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Later, studies (Okay et al, 2004;Seeber et al, 2004;Kanbur et al, 2007) have shown that this interpretation is inconsistent with the land data requiring north-dipping reverse fault, indicating an obvious misinterpretation of the seismic profile by Okay et al (1999). At that point, the main question is why and how this misinterpretation is possible.…”
Section: Introductionmentioning
confidence: 90%
“…The results of Kanbur et al (2007) have clearly shown the importance of the advanced stacking process in interpreting the multichannel reflection data profile across the complex structure of the Northern strand under the western Marmara Sea. The main objective in this study is to clarify the inconsistency between the interpretations of the seismic reflection profile (profile 3 in Fig.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations